2011
DOI: 10.1016/j.ijgo.2011.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the levonorgestrel‐releasing intrauterine system in uterine leiomyoma

Abstract: Use of the LNG-IUS appears to lead to a significant reduction in the uterine volume of women with menorrhagia, as well as reducing the MBL in women with uterine leiomyomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 19 publications
(26 reference statements)
2
33
1
Order By: Relevance
“…Kriplani et al reported 97.4% reduction in PBAC scores in myoma patients at 12 months with significant reduction of mean uterine volume. 19 However, similar to the findings in our study, they did not find any significant reduction in the volume of the myoma per se. Other studies have found satisfactory outcomes with LNG-IUS for fibroids less than 2.5cm, but not for those measuring more than 2.5cm.…”
Section: Discussionsupporting
confidence: 91%
“…Kriplani et al reported 97.4% reduction in PBAC scores in myoma patients at 12 months with significant reduction of mean uterine volume. 19 However, similar to the findings in our study, they did not find any significant reduction in the volume of the myoma per se. Other studies have found satisfactory outcomes with LNG-IUS for fibroids less than 2.5cm, but not for those measuring more than 2.5cm.…”
Section: Discussionsupporting
confidence: 91%
“…A.Kriplani et al concluded that non-receptiveness of certain uteri can be the cause of expulsion. 12,14 In our study we did not find any significant reduction in fibroid size after 6 months. This is in corroboration with the study by A. Kriplani et al who did not find any significant change in leiomyoma volume even after 2 years of LNG-IUCD insertion.…”
Section: -12contrasting
confidence: 61%
“…In contrast to this, Magal Haes et al found significant change in leiomyoma volume after 3 years. [14][15][16][17] Patients with anovulatory cycles suffer from loss of progesterone effect on the endometrium leading to proliferation of endometrium due to unopposed action of estrogen. Also, the recent theory suggests that the absence of progesterone results in reduced endometrial stromal cell factor, reduced plasminogen activator inhibitor-1 production, increased matrix metalloproteinase activity and increased angiogenic factor expression.…”
Section: -12mentioning
confidence: 99%
“…23 Recently, Kriplani et al have evaluated efficacy of the LNG-IUS in reducing menstrual blood loss in menorrhagia associated with myoma and idiopathic menorrhagia in Indian women. 22 LNG-IUS resulted in high and sustained reduction of menstrual blood loss in both groups (Figure 3). …”
Section: Indian Evidence Of Lng-iusmentioning
confidence: 93%
“…The details of these studies are given in Table 1. 5,[19][20][21][22][23][24] Gupta et al reported 97% reduction in menstrual blood loss with LNG-IUS, at the end of one year. 20 Anemia is very common in women suffering from heavy monthly bleeding.…”
Section: Indian Evidence Of Lng-iusmentioning
confidence: 99%